In vitro cytotoxic and molecular effects of metoprolol, alone or combined with cisplatin, on colon cancer cells - Al-Saady, Teeb Ali; Ibrahim, Ooroba M. S.; Al-Hussaniy, Hany Akeel (Pharmakeftiki, 2025)
Colorectal cancer ranks among the most prevalent malignancies worldwide, with surgical interventions frequently associated with substantial postoperative mortality and complications. Contemporary therapies often target molecular pathways such as the epidermal growth factor receptor and vascular endothelial growth factor. Recently, antihypertensive agents have been investigated for their potential anticancer properties, though results remain inconclusive. This study has assessed the cytotoxic effects of metoprolol, both as a monotherapy and in combination with cisplatin, on the SW480 colon cancer cell line using the MTT assay. Cisplatin achieved the highest cytotoxic activity at a concentration of 62.5 µg/mL, while metoprolol alone exhibited maximal cell-killing effects at 1,000 µg/mL. Notably, the combination of metoprolol (1,000 µg/mL) with cisplatin (15.6 µg/mL) demonstrated the most pronounced cytotoxic effect, thereby indicating potential synergistic activity. The findings suggest the potential of repurposing metoprolol as an adjunctive agent in combination chemotherapy, in order to enhance therapeutic outcomes in colorectal cancer treatment.